Real-time ultrasound-guided comparison of adductor canal block and psoas compartment block combined with sciatic nerve block in laparoscopic knee surgeries - Messeha, Medhat M. (Anesth Essays Res, 2016)
BACKGROUND: Lumbar plexus block, combined with a sciatic nerve block, is an effective locoregional anesthetic technique for analgesia and anesthesia of the lower extremity. The aim of this study was to compare the clinical results outcome of the adductor canal block versus the psoas compartment block combined with sciatic nerve block using real time ultrasound guidance in patients undergoing elective laparoscopic knee surgeries. PATIENTS AND METHODS: Ninety patients who were undergoing elective laparoscopic knee surgeries were randomly allocated to receive a sciatic nerve block in addition to lumbar plexus block using either an adductor canal block (ACB) or a posterior psoas compartment approach (PCB) using 25 ml of bupivacine 0.5% with adrenaline 1:400,000 injection over 2-3 minutes while observing the distribution of the local anesthetic in real time. Successful nerve block was defined as a complete loss of pinprick sensation in the region that is supplied by the three nerves along with adequate motor block, 30 minutes after injection. The degree of motor block was evaluated 30 minutes after the block procedure. The results of the present study showed that the real time ultrasound guidance of PCB is more effective than ACB approach. Although the sensory blockade of the femoral nerve achieved equally by both techniques, the LFC and OBT nerves were faster and more effectively blocked with PCB technique. Also PCB group showed significant complete sensory block without need for general anesthesia, significant decrease in the post-operative VAS and significant increase time of first analgesic requirement as compared to the ACB group. RESULT AND CONCLUSION: The present study demonstrates that blockade of lumber plexus by psoas compartment block is more effective in complete sensory block without general anesthesia supplementation in addition to decrease post-operative analgesic requirement than adductor canal block.